HUBUNGAN CHEMOTHERAPY INDUCED NAUSEA AND VOMITING (CINV) TERHADAP ASUPAN MAKAN DAN STATUS GIZI PASIEN KANKER PAYUDARA - Mutia Amalina Dewi (2020)
Breast cancer is a malignancy in the breast comes from glandular cells, glandular ducts, and another breast tissue. Breast cancer is the highest cause of cancer that occurs in women with a percentage of 30.9%. Chemotherapy is considered the most frequently chosen treatment by patients and 24.9% of cancer patients choose this treatment. Chemotherapy Induced Nausea and Vomiting (CINV) syndrome is a side effect that often arises and is the biggest problem in chemotherapy treatment. The purpose of this study was to determine the relationship of CINV syndrome to food intake and nutritional status of breast cancer patients. The research method used Literature Review with comprehensive data collection from 2015 to 2020 discussed at least one topic related to research. There were 26 studies related to the topic being reviewed. The results of the study stated that the factors influence the incidence of CINV include the type of chemotherapy regimen, the patient's age, psychological disorders, and a history of nausea and vomiting. Nutrient intake of breast cancer patients is lower compared to people without cancer and decreases during chemotherapy. A decrease in body weight and nutritional status in breast cancer patients is caused by low food intake which is influenced by the side effects of chemotherapy. The conclusion of this study is the incidence of CINV caused by chemotherapy associated with decreased food intake and nutritional status of breast cancer patients.